Remote sensing techniques applied to slope failure analysis - Riedel, P. S.; Rodrigues, J. E.; Mattos, J. T. (A A Balkema Publishers, 1998)
The paper evaluates the applicability of products of remote sensing in studies related to the structural conditionings of slope stability in saprolites, usually conducted through field surveys. In this article we use a regional approach concentrating on an area of lane duplication of a major highway. In that area, resistance reduction to stress and the low cohesions of muscovite saprolites - schists and gneiss which are associated to geological discontinuities, all result in inumerous instabilities. The joints and foliations were extracted from satellite images as well as aerial photographs. Following that, the study area was divided into various sectors based on the directions and dips of the foliation. Different relationships between the structures and the slopes were analyzed in order to indicate the most feasible type of slope failure in each sector of analysis. The aim of the study is to subsidize further detailed future research.